Traumatic Brain Injury: Patient Characteristics, Hospital Costs and Trends Over Time - Pankaj A. Patel; Peter J. Mallow; Mary Vassar; John A. Rizzo; Bhavik J. Pandya; Denise T. Kruzikas (Journal of Health Economics and Outcomes Research)
**Background:** Traumatic brain injury (TBI) is an increasingly diagnosed condition, but the trends in TBI visits and the cost of which have not been quantified from the hospital perspective.